Patient-reported outcomes after treatment for clinically localized prostate cancer: A systematic review and meta-analysis. (May 2018) - Ávila, Mónica; Patel, Laila; López, Silvia; Cortés-Sanabria, Laura; Garin, Olatz; Pont, Àngels; Ferrer, Ferran; Boladeras, Ana; Zamora, Victor; Fosså, Sophie; Storås, Anne H.; Sanda, Martin; et al.
Highlights: Many PRO studies but data still very scarce beyond two years of follow-up. Surgery produces sexual and incontinence deterioration but improves urinary symptoms. External radiotherapy has moderate sexual yet small incontinence & bowel side effects. Brachytherapy causes small incontinence and urinary, sexual and bowel side effects. The few studies on high-intensity focused ultrasound and active surveillance show no statistically significant worsening. Abstract: Background: The aim of this systematic review is to assess the impact of primary treatments with curative intention in patients with localized prostate cancer, measured with Patient-Reported Outcomes (PROs), and to examine differences among modalities within treatments. Methods: We conducted a systematic literature search for January 2005-March 2017 following PRISMA guidelines, including longitudinal studies measuring disease-specific PROs in localized prostate cancer patients with a follow-up from pre- to post-treatment (≥1 year). Two reviewers independently extracted data and assessed risk of bias. The study is registered in PROSPERO: CRD42015019747. Results: Of 148 identified studies, 60 were included in the meta-analyses. At the 1st year, radical prostatectomy patients showed small urinary irritative-obstructive improvement (0.37SD 95%CI 0.30, 0.45), but large deterioration for sexual function and incontinence with high heterogeneity (I 2  = 77% and 93%). Moderate worsening in external radiotherapy patients for sexual function (−0.46SD 95%CI −0.55, −0.36), small urinary incontinence (−0.16SD 95%CI −0.23, −0.09) and bowel impairment (−0.31SD 95%CI −0.39, −0.23). Brachytherapy patients presented small deterioration in urinary incontinence (−0.29SD 95%CI −0.39, −0.19), irritative obstructive symptoms (−0.35SD 95%CI −0.47, −0.23), sexual function (−0.12SD 95%CI −0.24, −0.002), and bowel bother (−0.27SD 95%CI −0.42, −0.11). These patterns persisted up to the 5th year. High-intensity focused ultrasound and active surveillance only have results at 1st year, showing no statistically significant worsening. Conclusions: No remarkable differences in PRO appeared between modalities within each treatment. Nowadays, available evidence supports brachytherapy as possible alternative to radical prostatectomy for patients seeking an attempted curative treatment limiting the risk for urinary incontinence and sexual dysfunction.